Tracking Affective Labour for Agility in the Quantified Workplace. (September 2018) - Moore, Phoebe V
Sensory and tracking technologies are being introduced into workplaces in ways Taylor and the Gilbreths could only have imagined. New work design experiments merge wellness with productivity to measure and modulate the affective and emotional labour of resilience that is necessary to survive the turbulence of the widespread incorporation of agile management systems, in which workers are expected to take symbolic direction from machines. The Quantified Workplace project was carried out by one company that fitted sensory algorithmic devices to workers' computers and bodies, which, this article argues, identify workers' so-called agility and reveal management practices that track affective and emotional labour, categorized in the project as stress, subjective productivity and wellbeing. Capital's accelerated attempts to capture more areas of work and workers' capacities facilitate the conversion of labour power into a source of value but also results in alienation and abstraction. Participants' resistance to participation in the Quantified Workplace reveals tensions in the labour process when affect is measured in processes of corporate change.